Urban models and Green infrastructure in the Latin American cities. An analysis of Buenos Aires city (Huellas, 2019)
There exists an important tradition in the formulation of urban models to describe and study urban socio-spatial structures. From the initial contributions of the 1920s until the 1950s these have emphasized the determination of specific spatial configurations (rings, sectors, multiple nuclei) and, in the last decades of the century, integrating proposals were generated. In the case of Latin American cities these specific basic configurations are combined, new ones arise and specific adjustments are made. Considering that Geography can be defined as a science that studies the relationship between man and the environment from a spatial point of view, the present study aims to analyze the green infrastructure such as specific land use in its urban-regional model distribution. From a systemic point of view, urban models oriented to the definition of the social map and green infrastructure focus their attention on the human and natural components in a link that will allow to advance in the improvement of the quality of life of the population and the urban resilience through diverse environmental services. An empirical approach will be presented from the case of Buenos Aires city, one of the largest Latin American urban areas.
Keywords: Urban Models; Green Infrastructure; Social Map